Fe-N-C Electrocatalysts with Densely Accessible Fe-N4 Sites for Efficient Oxygen Reduction Reaction - Zhou, Yazhou; Chen, Guangbo; Wang, Qing; Wang, Ding; Tao, Xiafang; Zhang, Tierui; Feng, Xinliang; Mullen, Klaus (Advanced Functional Materials, 2021)
The development of iron and nitrogen co-doped carbon (Fe-N-C) electrocatalysts for the oxygen reduction reaction (ORR) in proton-exchange membrane fuel cells (PEMFCs) is a grand challenge due to the low density of accessible Fe-N4 sites. Here, an in situ trapping strategy using nitrogen-rich molecules (e.g., melamine, MA) is demonstrated to enhance the amount of accessible Fe-N4 sites in Fe-N-C electrocatalysts. The melamine molecules can participate in the coordination of Fe ions in zeolitic imidazolate frameworks to form Fe-N6 sites within precursors. These Fe-N6 sites are then converted into atomically dispersed Fe-N4 sites during a pyrolytic process. Remarkably, the Fe-N-C/MA exhibits a high single-atom Fe content (3.5 wt.%), a large surface area (1160 m2 g−1), and a high density of accessible FeN4 sites (45.7 × 1019 sites g−1). As a result, Fe-N-C/MA shows a much enhanced ORR activity with a half-wave potential of 0.83 V (vs the reversible hydrogen electrode) in a 0.5 m H2SO4 electrolyte solution and a good performance in a PEMFC system with an activity of 80 mA cm−2 at 0.8 V under 1.0 bar H2/air. This work offers a promising approach toward high-performance carbon-based ORR electrocatalysts.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Fe-N-C catalysts; nitrogen-rich molecules trapping; oxygen reduction reaction; proton exchange membrane fuel cells; site density